الكفايات التدريسية ودرجة تطبيقها لدى طلاب التربية الميدانية في كلية المعلمين بجامعة طيبة من وجهة نظر الطلاب أنفسهم ومشرفيهم الأكاديميين - الجهني، عوض زريبان عودة الزايدي (الجامعة الأردنية - عمادة البحث العلمي, 2011)
تهدف الدراسة إلى تعرف الكفايات التدريسية، ودرجة تطبيقها لدى طلاب التربية الميدانية في كلية المعلمين بجامعة طيبة من وجهة نظر الطلاب أنفسهم ومشرفيهم الأكاديميين. ولتحقيق أغراض الدراسة استخدم الباحث استبانتين، اشتملت كلتاهما على قائمة من الكفايات التدريسية، وقد تم تقسيم الكفايات التدريسية إلى أربعة مجالات رئيسية لكلتا الأداتين وهي (كفاية الأهداف والتخطيط – كفاية التدريس وأداة الصف والمادة العلمية– كفاية الوسائل التعليمية والأنشطة العملية– كفاية التقويم) وقد تكونت العينة من (115) طالباً لخمسة تخصصات، وتم التأكد من صدق الأداتين وثباتهما بعرضهما على مجموعة من المحكمين، وقد بلغ ثبات أداة عينة المشرفين الأكاديميين (0.96) بينما بلغ ثبات أداة عينة الطلاب (0.94) وذلك حسب معادلة كرونباخ ألفا، وقد أسفرت الدراسة عن عدة نتائج أهمها: \ -\ أن أعلى نسبة مئوية من وجهة نظر الطلاب المعلمين أنفسهم كان لصالح كفاية التدريس وإدارة الصف والمادة العلمية، وقد بلغت (4.38) بينما جاء ترتيب هذه الكفاية من حيث وجهة نظر مشرفيهم الأكاديميين بالمرتبة الثالثة وبنسبة بلغت (3.81) والأولى كانت لصالح كفاية الأهداف والتخطيط وبنسبة بلغت (3.95) وهذه الكفاية من حيث وجهات نظر الطلاب المعلمين أنفسهم أصبحت في المرتبة الثانية بنسبة بلغت (4.34). \ -\ "عدم وجود فروق ذات دلالة إحصائية (α = 0.05) تعزى لمتغير التخصص، ولأثر المؤهل العلمي، ولسنوات الخبرة, باستثناء (مجال التدريس وإدارة الصف والمادة العلمية). \ -\ وجود فروق ذات دلالة إحصائية (α = 0.05) تعزى لأثر المرتبة الأكاديمية في جميع المجالات، وفي الأداة ككل". This study aimed at ascertaing the teaching competences and the extent to which they are manifested in practicum student teachers' performance from the perspective of the student teachers themselves and their academic supervisors. The study made use of two questionnaires both of which included a list of teaching competences. The teaching competences were divided into four main domains. These were (1) objectives and planning; (2) teaching, classroom management and knowledge of subject matter; (3) teaching aids and practical activities; and (4) evaluation. The study sample consisted of 115 students belonging to five specializations. The validity and reliability of the questionnaires were assessed by a jury of specialists The Alpha Cronbach reliability coefficient for the questionnaire directed to academic supervisors was.96 and was.94 for the questionnaire directed to student teachers. \ Results of the study indicated the following: \ -\ The highest percentage from students teachers' perspective went to the competence of teaching, classroom management and knowledge of subject matter (mean = 4.38) which was given the third rank by whereas the academic supervisors (mean =3.81). Academic supervisors gave the first rank to the competence of objective and planning (mean = 3.95) which was given the second rank by student teachers (mean = 4.34). \ -\ There were no statistically significant differences amongst academic supervisors in their perceptions of the teaching competences at the level of.05 due to the variables of qualifications or teaching experience or academic position, except for the competence of teaching, classroom management and knowledge of subject matter. \ -\ There were no statistically significant differences at the level of.05 due to teaching experience in all domains and in instrument as a whole with the exception of the domain of teaching, classroom management and knowledge of subject matter. Differences in this respect were in favour of those who have ten and more years of teaching experience. \ -\ There were statistically significant differences at the level of.05 in all domains and in the instrument as a whole due to the variable of academic rank
807866 783234
Keywords: التربية العملية -- السعودية -- جامعة طيبة -- كلية المعلمين -- الطلاب المعلمون -- المهارات التدريسية -- تدريب المعلمين قبل الخدمة -- طرق التدريس -- الوسائل التعليمية -- المشرفون التربويون -- التقييم التربوي